INTERPRETATION OF HIGH RESOLUTION AEROMAGNETIC AND LAND SATELLITE IMAGE OVER PART OF THE NORTH-CENTRAL BASEMENT COMPLEX: IMPLICATION FOR GROUNDWATER EXPLORATION - JONATHAN, BARKA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Considering the significance of groundwater to population growth, this study interprets high resolution aeromagnetic and land satellite imagery data to explore prospective areas for groundwater occurrence in part of the north-central Basement Complex of Nigeria. The study area lies between longitudes 5030' – 7000' E and latitudes 9030' – 10030' N. To achieve this objective, high resolution aeromagnetic data covering the study area was subjected to magnetic residual separation and analytical signal using Oasis Montaj version 8.4. The Land satellite imagery data was also subjected to false colour composite analysis using ILWIS version 3.3 software. Combination of this analysis aided in mapping of lineaments within the study area. Result of lineaments mapping from analytical signal and land satellite images shows high density lineaments around Wushishi, Zungeru, Tegina Kagara, Pandogari, Alawa, Gurmana and low density lineaments around Bobi, Kuta, Guni, Minna, Tenenge. These lineaments having a dominant trend in the NE-SW and NW-SE, E-W minor directions were interpreted as joints, veins, faults, foliations and lineation of outcrops. Field studies in Tegina, Zungeru and Wushishi falling within areas with high lineament density revealed good groundwater yield from motorized pumps, hand pumps and hand dug wells. This is contrary to what was observed in Gidan Gwari an area attributed to low lineament density where only one hand bore hole out of the seven drilled boreholes was productive.